Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3324/haematol.12249
|View full text |Cite
|
Sign up to set email alerts
|

Transient global amnesia associated with the infusion of DMSO-cryopreserved autologous peripheral blood stem cells

Abstract: Dimethylsulfoxide (DMSO) is a solvent commonly used for the cryopreservation of autologous peripheral blood stem cells (APBSC). Side effects upon infusion of DMSO-cryopreserved APBSC mainly consist of nausea, emesis, chills, rigors, and cardiovascular events, such as bradyarrhythmia or hypotension. We report the case of a patient who received DMSO-cryopreserved APBSC after myeloablative chemotherapy for a relapsing lymphoma. The patient developed a rare reaction during the infusion manifesting as transient glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The earliest reports of DMSO toxicity during stem cell infusion describe characteristic side effects such as nausea, vomiting, abdominal pain, chills and fever. 1,2 Rare but serious side effects of cryopreserved products include severe respiratory depression, 7 neurotoxicity resulting in amnesia, loss of consciousness or seizure 5,6 and fatal cardiac arrhythmia. 4 Efforts aimed at reducing the DMSO content of infused grafts either by washing or other means have resulted in a reduction of ARs among some studies, 8,9 but not others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest reports of DMSO toxicity during stem cell infusion describe characteristic side effects such as nausea, vomiting, abdominal pain, chills and fever. 1,2 Rare but serious side effects of cryopreserved products include severe respiratory depression, 7 neurotoxicity resulting in amnesia, loss of consciousness or seizure 5,6 and fatal cardiac arrhythmia. 4 Efforts aimed at reducing the DMSO content of infused grafts either by washing or other means have resulted in a reduction of ARs among some studies, 8,9 but not others.…”
Section: Introductionmentioning
confidence: 99%
“…These range from common mild reactions including nausea, vomiting, flushing, fever, chills and cough [1][2][3] to rare life-threatening reactions affecting the cardiovascular, respiratory and neurological systems. [4][5][6][7] Infusion-related ARs have been attributed to both cellular and non-cellular elements within the cellular therapy product (CTP). In addition to the desired CD34 + hematopoietic stem cells, CTPs contain a wide variety RBC, cytokines and WBC including mature granulocytes, lymphocytes and monocytes, all of which may contribute to infusion-related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model data and clinical observations indicated that this agent may affect the vascular system leading to prolonged vasoconstriction and cerebrovascular ischaemia, [1][2][3][4][5]8 even though neuroimaging did not display a 'vascular' pattern in all of the cases (Table 1). Idiosyncratic mechanisms, a predisposing genetic background and a direct effect of DMSO on neural cell metabolism have also been hypothesized.…”
mentioning
confidence: 99%
“…Idiosyncratic mechanisms, a predisposing genetic background and a direct effect of DMSO on neural cell metabolism have also been hypothesized. [5][6][7]9 Whether the occurrence of neurotoxicity is related to the amount of DMSO infused (maximal recommended dose is 1000 mg/kg or 10 ml/kg of a 10% solution) and/or to infusion rate also remains controversial. 7 Our patient developed symptoms after receiving only 10.5 ml of DMSO at a low infusion rate, suggesting that patient-related factors might have also contributed to the development of neurotoxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation